Особливості використання Apache Kafka у розподілених системах реального часу - Погорєлова, Л. А. (ХНУРЕ, 2024)
The article provides a detailed description of distributed systems for real time data analysis and processing. In the modern world, where speed, accuracy, and timeliness of information are becoming key success factors, understanding, and using Big Data and data processing is extremely important. To achieve this goal, it is necessary to use appropriate tools and modern approaches that allow efficient processing, analysis, and use of data. Apache Kafka is one of such tools. It supplies useful methods of communication between producers and consumers. The basic principles of the message broker architecture were considered.
Keywords: Apache Kafka; розподілені системи реального часу